Democratic Policing: POLRI Neutrality in Democratic Election - Idris Sandiya,; Basir, S. (Technium Social Sciences Journal, 2021)
The democratic party in the form of elections and presidential elections is a crucial moment for the survival of the Nation and a moment that is prone to abuse of power, corruption, and social conflict. In relation to the relationship between the nation, democracy, and neutrality, it becomes essential to ensure the neutral attitude of the nation apparatus at the time of the election. This is both bureaucratic, such as ASN, and instruments of public order and national resilience such as TNI/POLRI. The ministry organized by bureaucratic officials is based on professionalism, not because of political interests. Neutrality also means that governments should not take sides in the group's interests but act based on professionalism with credible individual capabilities and a high level of capability. This article seeks to relate the views of figures such as Marx, Weber, and Hegel concerning bureaucratic neutrality, in this case, the role of POLRI in elections and presidential elections, with the principles of democratic policing. This research argues that referring to the view of bureaucratic neutrality, the impartiality of the nation through its apparatus is a natural phenomenon, closely related to the power relationship between the Police and the ruling group, and contains elements of abuse of power. Thus, in this understanding, this phenomenon then contradicts the principle of democratic policing. In this context, the author sees the implementation of a neutral bureaucracy and POLRI that implement democratic policing has not been reflected in implementation and security during elections and presidential elections.